Human pappilomavirus genotype in cervical tissue of patients with Cervical Intraepithelial Neoplasia (CIN) 1, CIN 2, and CIN 3 - Gondo Mastutik; Rahmi Alia; Alphania Rahniayu; Anny Setijo Rahaju; Renny I’tishom; Suhartono Taat Putra (Majalah Obstetri dan Ginekologi, 2016)
Objectives: to determine the genotype of HPV in patients with precancerous lesions of cervical tissue.Materials and Methods: An observational study with cross sectional study of patients paraffin block CIN1, CIN2, CIN3 was conducted in Dr Soetomo Hospital. HPV DNA was extracted from paraffin blocks, then performed PCR and genotyping of HPV. The sample consisted of 28 patients with cervical tissue paraffin blocks CIN1, CIN2 and CIN3. Patients aged between 26-74 years (standard deviation 10,12).Results: HPV genotypes that infect patients with CIN1 were HPV16 and 18, CIN2 were HPV16 and 52 and CIN3 were HPV16, 67, and combined infection HPV16/67 and HPV52/67. HPV genotypes in a single infection were 26/28 (HPV16, HPV18, HPV52 and HPV67), and multiple infections were 2/28 (HPV16/67 and HPV52/67).Conclusion: The most dominant HPV genotypes infect patients with precancerous lesions of the cervix were HPV16, HPV67, HPV52, and HPV18.